Implementation of Islamic Financial Instruments for the Welfare of the Labuhanbatu Community - Dini Yunila Tanjung; Saparuddin Siregar; Yenni Samri Juliati Nasution (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The main problem of this research is to determine the implementation of Sharia financial instruments for the benefit of the Labuhanbatu community. This research aims to find out how ZIS (Zakat, Infaq, and Sadaqoh) is implemented at BAZNAS Labuhanbatu. This research uses a qualitative approach using a descriptive approach to collect data through observation, interviews, documentation, and data sources from interviews with the BAZNAS Management of Labuhanbatu Regency. The findings of this article are that ZIS management is carried out through the collection and distribution of funds collected from OPD and individuals by BAZNAS Labuhanbatu and through socialization while still providing a direct distribution mechanism according to established procedures. This research concludes that the implementation of Sharia financial instruments in Labuhanbatu has an influence on achieving community welfare (namely ZIS). The measure of community welfare was developed from 5 indicators, some of which have been implemented by Baznas.